The impact of fiber arrangement and advective transport in porous electrodes for silver-based thermally regenerated batteries. (20th August 2021) - Cross, Nicholas R.; Hall, Derek M.; Lvov, Serguei N.; Logan, Bruce E.; Rau, Matthew J.
Highlights: Modelled flow, metal deposition, and power in Ag-TRAB electrodes. Vortex formation between fibers affected surface concentrations and power density. A staggered electrode fiber arrangement resulted in increased Ag deposition rates. Low void fractions having higher ohmic contributions and less uniform deposition. A variable void fraction electrode balanced battery performance with longevity. Abstract: The silver-based thermally regenerative ammonia battery is a new technology for converting low-grade waste heat (<100 °C) to electrical power. These hybrid flow batteries are charged using energy derived from waste heat, rather than electrical power, and can be cycled hundreds of times without a decrease in performance. Design factors that impact operational conditions and performance are needed to improve reliability and increase power densities. For example, the structure of the porous electrodes could alter silver deposition rates and porosities of the electrodes during operation, leading to preferential flow paths from clogging of pores that would impact cycle longevity and power. A 2D numerical model was therefore used to study the relationship between fluid flow and electrodeposition in the porous electrodes using cylinders in cross-flow to represent the internal structure of a porous carbon fiber electrode. Lower void fractions increased peak power by 2.5% to 7.1% but resulted in pore clogging 3–5 times faster due to nonuniform deposition. It was found that staggered fiber arrangements maintained higher surface concentrations and 4.9% to 8.9% higher peak power compared to in-line fiber arrangements with the same void fraction while also displaying less dependence on fluid velocity due to efficient advection of reactants. An electrode with variable void fraction was designed to increase peak power by 7.5% but the pores clogged 23% faster compared to a similar electrode with a homogeneous void fraction. Graphical abstract: Image, graphical abstract